2016
DOI: 10.1038/srep39660
|View full text |Cite
|
Sign up to set email alerts
|

Bioorthogonal chemical imaging of metabolic activities in live mammalian hippocampal tissues with stimulated Raman scattering

Abstract: Brain is an immensely complex system displaying dynamic and heterogeneous metabolic activities. Visualizing cellular metabolism of nucleic acids, proteins, and lipids in brain with chemical specificity has been a long-standing challenge. Recent development in metabolic labeling of small biomolecules allows the study of these metabolisms at the global level. However, these techniques generally require nonphysiological sample preparation for either destructive mass spectrometry imaging or secondary labeling with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 62 publications
1
52
0
Order By: Relevance
“…Later Chen et al created different vibrational colors for EdU by isotope-editing the alkyne moiety 21 (Figure 1E–F). With these multi-color labels and applying them in a pulse-chase manner, Hu et al recently showed that even different stages of DNA synthesis could be visualized in the same nuclei of neural progenitor cell 22 (Figure 1G–I). Thus, the live-cell imaging capability of SRS as well as the multiplexing potential of EdU makes it possible to reveal cell cycle dynamics in complex tissue or animal samples.…”
Section: Nucleic Acid Metabolismmentioning
confidence: 99%
See 3 more Smart Citations
“…Later Chen et al created different vibrational colors for EdU by isotope-editing the alkyne moiety 21 (Figure 1E–F). With these multi-color labels and applying them in a pulse-chase manner, Hu et al recently showed that even different stages of DNA synthesis could be visualized in the same nuclei of neural progenitor cell 22 (Figure 1G–I). Thus, the live-cell imaging capability of SRS as well as the multiplexing potential of EdU makes it possible to reveal cell cycle dynamics in complex tissue or animal samples.…”
Section: Nucleic Acid Metabolismmentioning
confidence: 99%
“…With all the tools developed for imaging nucleic acid, amino acids, fatty acid, and choline by SRS as previously described, Hu et al further studied complex metabolism with all these vibrational tags in live rat brain hippocampal tissues and the metabolic response after traumatic injury with subcellular resolution 22 . In the dentate gyrus of hippocampus, they found heterogeneous incorporations of amino acids, choline and fatty acids at subcellular level.…”
Section: Brain Imaging and Metabolismmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, our lab and others have developed methods to visualize lipogenic activities in living tissues by supplying deuterium-labeled fatty acids (D-FAs), such as palmitic acid, oleic acid, and arachidonic acid, and imaging C-D bonds in newly synthesized lipids [30][31][32][33] . However, DO-SRS is fundamentally different from those previous methods because D2O is a noninterfering probe that does not change native metabolism and is a non-carbon tracer that can probe activities of de novo lipogenesis.…”
Section: Optical Imaging Of De Novo Lipogenesis Via Do-srsmentioning
confidence: 99%